Unusual histopathological findings of lupus miliaris disseminatus faciei: A case report - Pooja Bains; Priya Kapoor; Navleen Kaur (Galenos Publishing House, 2024)
Lupus miliaris disseminatus faciei (LMDF) is a chronic granulomatous disorder affecting the face in young adults with sudden eruption of asymptomatic skin colored to red-brown papules on cheeks, eyelids and few extrafacial sites including ears and neck. There has been disputation about the origin of the disease, but the consensus is that it is an immune response to the pilosebaceous unit. Various histopathological studies have found granulomas in association with pilosebaceous units. The present case discusses the rare occurrence of foreign body granuloma surrounding a ruptured infundibular cyst in the case of LMDF. The role of a ruptured infundibular cyst in the induction of an inflammatory reaction resulting in the development of granuloma in LMDF cannot be ruled out.